Les opportunités marketing de Twitter : dépasser le discours « SoLoMo » - Jean-Claude Domenget (Netcom)
Sociotechnical approach followed in this paper evaluates the real marketing opportunities of Twitter. It starts from a discourse analysis "SoLoMo" (for Social, Local and Mobile), integrating social logic involved, analyzing the incentives of the device as well as the limitations encountered. Mapping is then presented distinguishing spaces for marketing actions on the social web. It leads to emphasize the benefits of Twitter as "lighthouse" visibility device, focused on content sharing around interests. However, despite the opportunities related to strengthening the brand in customer loyalty, prescription ordinary relationship marketing, or on e-reputation company, several limitations are discussed. All raises questions about the underlying trend in the current industrialization of the online presence of companies and brands.